2009
DOI: 10.1093/sleep/32.9.1191
|View full text |Cite
|
Sign up to set email alerts
|

Lucid Dreaming: a State of Consciousness with Features of Both Waking and Non-Lucid Dreaming

Abstract: Our data show that lucid dreaming constitutes a hybrid state of consciousness with definable and measurable differences from waking and from REM sleep, particularly in frontal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
325
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(347 citation statements)
references
References 23 publications
15
325
2
5
Order By: Relevance
“…In order to go beyond the correlational data regarding the neural correlates of dream lucidity as suggested by previous EEG and fMRI studies (Dresler et al, 2012;Voss et al, 2009), we aimed in this study to experimentally manipulate the activation of the prefrontal brain cortex and test the neurobiological basis of dream lucidity. Anodal tDCS was applied during REM sleep to activate the DLPFC and -by modulating cortical excitability -should have had an effect on subjective experience of dreaming by increasing the probability of lucid dreaming.…”
Section: Tdcs Effects On Dream Luciditymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to go beyond the correlational data regarding the neural correlates of dream lucidity as suggested by previous EEG and fMRI studies (Dresler et al, 2012;Voss et al, 2009), we aimed in this study to experimentally manipulate the activation of the prefrontal brain cortex and test the neurobiological basis of dream lucidity. Anodal tDCS was applied during REM sleep to activate the DLPFC and -by modulating cortical excitability -should have had an effect on subjective experience of dreaming by increasing the probability of lucid dreaming.…”
Section: Tdcs Effects On Dream Luciditymentioning
confidence: 99%
“…Hobson et al (2000) have proposed that, during the lucid state, the previously deactivated DLPFC becomes reactivated, allowing directed thought, metacognition and awareness of being while in a dream state. Preliminary empirical evidence for this hypothesis has been obtained from a recent study (Voss, Holzmann, Tuin, & Hobson, 2009) which found that when participants become lucid, there is a shift in their EEG power, especially in the 40 Hz range and in frontal brain regions. Moreover, in lucid dreaming, EEG coherence is also largest in frontolateral and frontal areas (for all frequency bands, 1-45 Hz).…”
Section: Introductionmentioning
confidence: 98%
“…However, recent EEG findings indicate that lucid dreaming might correspond to an hybrid state of consciousness, with some EEG features more similar to those seen in wakefulness than in REM sleep (e.g. overall coherence levels, gamma power in frontal regions) (Voss, Holzmann, Tuin, & Hobson, 2009). While lucid dreaming is certainly an imperfect model of the dreaming brain, it offers some uniquely dissociated features of REM sleep and wakefulness, both at the mind and brain levels, which may usefully contribute to our understanding of the neural bases of consciousness.…”
Section: Integration Of Brain Imaging and Dream Datamentioning
confidence: 99%
“…In contrast to dreaming, lucid dreaming (LD) is a phenomenon in which dreamers can be aware of dreaming and sleeping, which resembles metacognitive activity during sleep (5,6). Furthermore, non-lucid dreamers are reported to suffer from metacognitive deficits (6).…”
Section: Introductionmentioning
confidence: 99%